Formulation of Effervescent Tablet From Extract of Durian (Durio zibethinus Murr.) Peels and Its Antioxidant Activity - Pramesti, Citra; Alighiri, Dante (Journal of Science and Technology Research for Pharmacy, 2023)
Durian (Durio zibethinus Murr.) is one of the seasonal fruits whose existence is abundant in Indonesia that leaves the waste of durian peels that are usually discarded after the durian fruit is consumed. While durian peel contains flavonoid, phenolic, alkaloid, steroid, saponin and a few terpenoid compounds based on durian fruit skin have a variety of pharmacological activities, one of which is as a natural source of antioxidants.The study aims to formulate durian fruit peels extract in an effervescent tablet preparation that is expected to be able to be one of the variations of natural antioxidants that can be easily consumed by society. The formula of effervescent tablets of durian fruit peels extract is made with variations in the concentration of Formula 1 dry extract of 0%, Formula 2 of 16%, Formula 3 of 20%, Formula 4 of 30%. The extraction method used in this study was the reflux method with 96% ethanol solvent. Effervescent tablets of durian skin extract were then tested for its antioxidant activity using the DPPH method and measured the value. In this study, durian peels extract was formulated into the form of an effervescent 1000 mg tablet preparation with variations in the concentration of dry extract 0%, 16%, 20% and 30%. All formulas showed the results of the evaluation of the physical properties of the granules and tablets were good and met the required standards. Formula 4 showed higher antioxidant activity compared to the other three formulas. This can be seen from the concentration of the added dry extract reaching 30%. Furthermore, formula 4 showed the smallest value of 117,7329 μg/mL, where the smaller the value of , the stronger its antioxidant activity. Based on these values, the formula 4 effervescent tablets are included in the moderate antioxidant activity.